Enrichment of low grade CH4 from N2/CH4 mixtures using vacuum swing adsorption with activated carbon. (16th January 2021) - Hu, Guoping; Zhao, Qinghu; Tao, Lefu; Xiao, Penny; Webley, Paul A.; Li, Kevin Gang
Highlights: CH4 /N2 separation was achieved with activated carbon and vacuum swing adsorption. A sensitivity analysis was conducted to achieve high product purity. Pressure equalization and heavy product purge steps have significant impacts on product purity. Recovery of low concentration CH4 has been demonstrated as both technically and energetically feasible. Abstract: Methane (CH4 ) is a cleaner fuel resource with relatively low carbon emissions and negligible particulate matters, heavy metals, and sulphur oxides, compared with those emission intensive fuels like coal. However, large amounts of CH4 emitted to the atmosphere drive significant greenhouse gas (GHG) effects due to the low value of its low concentration sources and technical difficulty of CH4 /N2 separation. Therefore, it becomes crucial to advance the technology for separating low concentration CH4 from N2 . In this study, a commercial activated carbon was used to separate CH4 from N2 with a 4-column vacuum swing adsorption (VSA) facility. Both light and heavy streams were firstly collected and stored in gas tanks, and then used for light/heavy purge. Four process modes involving A) 2-column and 8 steps, B) 3-column and 9 steps, C) 4-column and 16 steps, and D) 4-column and 20 steps were employed to investigate the effects of process design factors on their separation performance. Results showed that both pressure equalization and heavy product purge steps have significant impacts on product purity, recovery and productivity. In the case of 11.7 and 17.0% (CH4 ) feed gases, the methane products reached a purity around/above 30% and these gases can be compressed and transported for industrial utilization. Furthermore, the recovery of these low concentration methane gases will bring extra incentives with GHG mitigation benefits.